Carbon balance of forest management and wood production in the boreal forest of Quebec (Canada) - Giasson, Louis-Alexandre; Thiffault, Evelyne; Lebel, Luc; Carle, Jean-François (Frontiers in Forests and Global Change, 2023)
Management of boreal forests can increase terrestrial carbon sinks and reduce greenhouse gas (GHG) emissions to the atmosphere. A case study was conducted in the boreal balsam fir forests of Quebec (Canada), a commercially important region for forestry, to identify optimal management and wood production solutions that contribute to reducing GHG emissions to the atmosphere. Scenarios were based on a steady level of harvest and silvicultural activities over time and a stable flow of wood products to markets. Scenarios included: increases and decreases in the volume of harvested timber; the transition of harvesting activities from clearcuts (the most common practice in the region) to partial cuts; and changes in the rate of natural regeneration (the usual mode of regeneration) vs. plantations. All scenarios provided a carbon sink regardless of the time frame. Compared with other scenarios, reducing harvest levels increased the forest carbon sink in the short (10 to 20 years) and medium (20 to 50 years) terms. Also, for a similar harvest level, the increased use of partial cutting and planting increased the forest carbon sink. In the long term (over 50 years), strategies with low harvesting levels resulted in lower ecosystem carbon sequestration, even though they still had the lowest cumulative emissions. Nevertheless, higher harvesting levels could not be justified because the long-term increase in the forest ecosystem carbon sink could not offset higher emissions from wood products, particularly from short-lived paper products. Sensitivity analyses showed that improving sawmill efficiency and thus increasing the proportion of long-lived products was an important factor that can greatly reduce emissions. On the other hand, transportation distances between forest stands and sawmills had a relatively marginal impact on the overall carbon balance of forest management and wood production scenarios.